The Role of Heat Shock Proteins in Leukemia - Kliková, K; Pilchova, I; Stefanikova, A; Hatok, J; Dobrota, D; Racay, P (Klinicka onkologie, 2016)
Heat shock proteins (HSPs) HSP27, HSP70 and HSP90 are molecular chaperones; their expression is increased after exposure of cells to conditions of environmental stress, including heat shock, heavy metals, oxidative stress, or pathologic conditions, such as ischemia, infection, and inflammation. Their protective function is to help the cell cope with lethal conditions. The HSPs are a class of proteins which, in normal cells, are responsible for maintaining homeostasis, interacting with diverse protein substrates to assist in their folding, and preventing the appearance of folding intermediates that lead to misfolded or damaged molecules. They have been shown to interact with different key apoptotic proteins and play a crucial role in regulating apoptosis. Several HSPs have been demonstrated to directly interact with various components of tightly regulated caspase-dependent programmed cell death. These proteins also affect caspase-independent apoptosis by interacting with apoptogenic factors. Heat shock proteins are aberrantly expressed in hematological malignancies. Because of their prognostic implications and functional role in leukemias, HSPs represent an interesting target for antileukemic therapy. This review will describe different molecules interacting with anti-apoptotic proteins HSP70 and HSP90, which can be used in cancer therapy based on their inhibition.
Keywords: proteiny teplotního šoku; Heat-Shock Proteins; HSP70 Heat-Shock Proteins; apoptóza; Humans; proteiny tepelného šoku HSP27; lidé; proteiny tepelného šoku HSP70; leukemie; HSP27 Heat-Shock Proteins; Leukemia; proteiny tepelného šoku HSP90; Apoptosis; HSP90 Heat-Shock Proteins